Hot and Bothered: Applying the Five Elements Framework to the Climate Crisis - Shona Whitton; Georgina Grundy-Campbell (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
The climate crisis is exacerbating humanitarian crises and significantly impacting mental health and psychosocial wellbeing globally. This paper explores the application of Hobfoll’s five essential elements framework—promoting safety, calming, self-efficacy, connectedness, and hope—to address the mental health impacts of the climate crisis. Drawing from existing literature and practical experience, the paper examines how climate change affects mental health through multiple pathways, leading to increased rates of mental health conditions and psychological distress. The framework’s relevance to climate-related challenges is analyzed, offering practical guidance for mental health and psychosocial support practitioners and policymakers. The paper argues that integrating mental health considerations into climate action through this established framework can help communities build resilience and cope with climate-related stressors. While acknowledging limitations in current research, particularly regarding a lack of perspectives from the global South, this conceptual work provides a foundation for developing comprehensive responses to the mental health dimensions of the climate crisis. The paper concludes that applying the five elements framework, alongside integrated programming and cross-sector collaboration, offers a valuable approach for promoting community wellbeing in the face of unprecedented environmental challenges.